A systematic review of interventions to promote social support and parenting skills in parents with an intellectual disability. Issue 1 (21st January 2013) - Wilson, S.; McKenzie, K.; Quayle, E.; Murray, G.
Abstract The family support needs of parents with an intellectual disability (ID) are relatively unknown. This paper reviewed two types of intervention for parents with ID: those designed to strengthen social relationships and those teaching parenting skills. A literature search was conducted using electronic databases and a limited number of evaluative studies were found. The evidence for interventions aimed at strengthening social relationships was inconclusive; although positive changes were observed, there were limitations in study design which restricted the generalizability of the results. The evidence for parental skills teaching suggested that behavioural based interventions are more effective than less intensive forms such as lesson booklets and the provision of normal services, although these studies also had limitations. There is a need for further large scale controlled studies in this area to provide clearer evidence and to explore additional factors relating to child, parent and family which may impact on outcomes.